Comparative study of healing time of canine non-infectious deep ulcerative keratitis between medical therapy alone and combined treatment with medical therapy and a nictitating membrane flap: A retrospective study - Kanokpich Imcharoon; Natawadee Pinyosnit; Pimpika Srilert; Tanakanok Ngampongsai; Vachira Hunprasit; Nalinee Tuntivanich; Orapun Jaturakan (Open Veterinary Journal, 2022)
Background: Canine non-infectious deep ulcerative keratitis is considered a severe ocular disorder that possibly can progress to perforation. Immediate treatment should be directed to stimulate corneal wound healing, control infection, and minimize self-trauma while eliminating the underlying causes. Aim: This retrospective study was aimed to compare the difference of non-infectious deep corneal wound healing time between cases treated with medical therapy alone and those treated with medical therapy combined with a nictitating membrane flap. Methods: The medical records at the Ophthalmology Clinic, Small Animal Teaching Hospital, Faculty of Veterinary Science, Chulalongkorn University between January 2018 and March 2020 were retrospectively reviewed. Sixty-six eyes (from 65 dogs) diagnosed with non-infectious deep ulcerative keratitis from the medical treatment group (n = 34) and the combined treatment group (n = 32) were included. The combined treatment group was prescribed the same conservative medical administrations plus a surgical nictitating membrane flap for 14 days. Results: Healing time was defined as the duration of time from the day that the dog had been diagnosed with deep ulcerative keratitis by a fluorescein staining test to the day that the corneal fluorescein stain was negative. Overall, the mean age of dogs with deep ulcerative keratitis was 10.49 ± 4.7 years. The disease was commonly evident in females more than males. Shih Tzu was the most prevalent dog breeds. The corneal healing time between dogs receiving medical therapy alone and those receiving combined treatment was not statistically significant (p = 0.386). Healing times were not significantly different between sex and breed (p = 0.41). The median corneal healing time for dogs older than 10 years in the combined treatments group (29.5 days; ranging from 20 to 46 days) was longer than for those receiving medical therapy alone (21 days; ranging from 9.5 to 30.5 days). Conclusion: Supportive therapy including a nictitating membrane flap is suggested in dogs prone to deep corneal ulcer not involving infection. Even though the healing time is not statistically significant, it acts as tissue bandage to reduce friction over the cornea, but it also alleviates the healing process by moistening the ocular surface. [Open Vet J 2022; 12(6.000): 815-821]